Salasa adulis as a novel dual-functional food additive for antimicrobial and antioxidant properties: experimental and theoretical approach - Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya; Abu Samah, Mohd Armi; Omar, Muhammad Nor; Ahmad, Mohammad Norazmi (Universiti Kuala Lumpur Branch Campus Malaysian Institute of Chemical and Bioengineering Technology, 2019)
Lipid oxidation and microbial contamination are the major contributors to quality and safety loss of food products. The addition of food additives such as antioxidant and antimicrobial can increase the shelf life of foods and influence the characteristics of foods favourably. Salasa adulis or salak seeds contain phenolic compounds that exhibited interesting biological properties which contribute to its use as a new potential source of natural antioxidant and antimicrobial agent. This research aim to identify a novel phenolic compound of S. adulis seeds as a new antioxidant and antimicrobial inhibitor. A method development using green chemistry approach, supercritical fluid extraction (SFE) was used to extract the phenolic compounds from S. adulis seeds. The SFE conditions were optimized using Response Surface Methodology (RSM) that investigated the interaction between three variables (pressure, temperature, and extraction time). The optimum condition was achieved at 5814.67 psi, 78.09 ℃, and 96.43 min. The antioxidant activity test was done using DPPH radical scavenging assay where the % DPPH radical scavenging activity was 89.39 ± 0.16 %. The combination of GC-MS and PCA method revealed the potentiality of benzeneethanamine, 2,5- difluoro-β,3,4-trihydroxy-N-methyl- (C5) as antimicrobial agent. The suitability of carbon dioxide as the solvent for supercritical fluid extraction to extract C5 was shown by COSMO RS. MEP was used to identify key structural features of C5 that are necessary for their activity and to investigate their interaction with β ketoacyl-acyl carrier protein synthase III (FabH). The insight of microbial inhibitory action by C5 was carried out by using molecular docking and revealed the binding affinity with E. coli FabH-CoA was -6.1 kcal/mol.